A hard (metal) case: Value of analytical scanning electron microscopy. (3rd May 2016) - Sporn, Thomas A.; Roggli, Victor L.
ABSTRACT: Exposure to hard metal (tungsten carbide) dust is a rare cause of interstitial lung disease. Although most cases have a distinctive morphology known as giant cell interstitial pneumonitis, other patterns have been described as well. In such cases, the true nature of the interstitial process may be difficult to recognize. We present a case with unusual morphological features in which analytical scanning electron microscopy (SEM) was used to detect the presence of tungsten as well as other metallic particles. A combination of careful exposure history and examination by analytical SEM is useful for arriving at the correct diagnosis in such difficult cases.